PENGGUNAAN VIDEO ANIMASI PADA KETERAMPILAN MENYIMAK CERITA DONGENG SISWA KELAS II SEKOLAH DASAR - Beby Zein Rismala; Ermawati Zulikhatin Nuroh (Kurikula : Jurnal Pendidikan, 2023)
The purpose of this study was to describe students' responses to the use of animated videos in listening to fairy tales for class II at SDN Bringinbendo 2, Taman District, Sidoarjo Regency. The researcher confirms that research on using animated video media in learning Indonesian on students' listening skills can be interested and active, So. Teachers must use media in order to students don't feel bored and easily understand, therefore when learning teachers don't only use the lecture method.Teachers must also be innovative in using media to be used during learning so that it can be in accordance with the desired learning, and students can also maximize learning, students are easy teachers who still tell fairy tales without using other media except thematic books that contain fairy tales "Ingenuity Grows Kindness” by reading it directly to students, and the teacher did not have time to make media because there was a lot of work. This has often been used so that students feel bored and mediocre in learning fairy tales. There are some students who do not listen because students feel bored and less interesting. This study used a descriptive qualitative method with a total of 10 students participating. This type of research uses case studies. This data collection by observation, questionnaires and interviews. Data collection techniques in this study used technical triangulation, data analysis used data reduction, data forms and conclusions. The findings show that animated videos are very suitable for listening to fairy tales because they make it easier for students to remember stories, knowing the story's message and animated videos make students more active, interested and enthusiastic. This media is very helpful for them in listening to fairy tales, and in this animated video there are animated images that can move and have sound.